If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) + -3x = -12 + -3x Reorder the terms: 2(-2 + x) + -3x = -12 + -3x (-2 * 2 + x * 2) + -3x = -12 + -3x (-4 + 2x) + -3x = -12 + -3x Combine like terms: 2x + -3x = -1x -4 + -1x = -12 + -3x Solving -4 + -1x = -12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -4 + -1x + 3x = -12 + -3x + 3x Combine like terms: -1x + 3x = 2x -4 + 2x = -12 + -3x + 3x Combine like terms: -3x + 3x = 0 -4 + 2x = -12 + 0 -4 + 2x = -12 Add '4' to each side of the equation. -4 + 4 + 2x = -12 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = -12 + 4 2x = -12 + 4 Combine like terms: -12 + 4 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 82-b=64 | | (x^2-x+2)(x-5)= | | 6=3-k | | 6x+9(x-3)=5(x-8) | | 82-b= | | 3m-m-m-m+2m=16 | | 4(x+9)=-3(2x-9)+4x | | 22x-10=0 | | 15=19+2(q-18) | | 9x-3(x-2)=2(x-3)+9 | | -6y=-20 | | -3x^2-30x^2-72x=0 | | -6y=-29 | | -s+6s+16s-20s=11 | | 9(x-9)+5x=9-5(x-8) | | 2(x+5)=3(4+x) | | 6y-7(y-3)=8-7(y-3) | | x+(x*.0825)=65.35 | | 6.3a+4.5/2=10.2 | | 5t+2t+2t-3t-3t-2=13 | | 59-e=58 | | 4(d-2.13)-2.66=3(d-2.27) | | -(5x-11)+4(3x+8)= | | -8x+10=-6x+20 | | 31x-8(3x-0.745)=6x+0.205 | | 2(x+5)+3(4+x)= | | 4x+5y-y+3= | | 2c+7=-5c+2 | | x^4-14x-120=0 | | 12y-9y-8y+7y=12 | | -9+y=-12 | | 7(p-5)=21 |